A Moderate Defense for Visual Arguments: Dynamic Existentialism and the Expansion of Argumentation Theory - Liao, Yanlin; Niu, Zihan (Informal Logic)

(untitled) (Informal Logic, 2025)
This paper critically examines the ongoing debate over the legitimacy of visual arguments and proposes a resolution to this issue. Using a type-theory framework, the legitimacy of visual arguments is addressed through two key sub-problems. First, the paper argues that visual arguments exist, with their existence grounded in dynamic existentialism. Second, it contends that visual argumentation theory can expand argumentation theory in both descriptive and normative aspects. The paper advocates for a moderate defense of visual arguments, offering a stronger foundation for future research in the field.